Relationship between Vegetation, Sky View Factor and Thermal Comfort: A Systematic Literature Review - Chiquetti, Simone Merino; Faria, João Roberto Gomes de (Revista Nacional de Gerenciamento de Cidades, 2022)
The relationship between urban morphology and thermal conditions has been subject of several scientific studies and, recently, the role of vegetation in this context has been investigated, aiming to understand its contributions to the improvement of thermal comfort in outdoor environments. This study aimed to understand the relationship between urban vegetation present in the sky view factor (FVC) and thermal comfort. A systematic literature review on the subject was carried out by applying an adaptation of the Preferred Reporting Items methodological approach for Systematic Reviews and Meta-Analyses (PRISMA), seeking to guarantee a transparent and replicable work. The evaluated materials were obtained through database searches using the terms vegetation AND “thermal comfort” AND “sky view factor” and selected by criteria defined by the “PICOS” strategy. parameters referring to the main characteristics of the researches and results achieved, through the reading and tabulation of data with the help of electronic spreadsheets. The results obtained highlight the growing interest in the subject in scientific research, but demonstrate a lack of studies in Latin American countries. It is also observed that most studies indicate a positive relationship between vegetation in the FVC and thermal comfort, with the incidence of negative results at night, winter or interference with wind speed. Such scenarios indicate the need for more studies that seek better understand the particularities of the behavior of urban vegetation in different ways. between climatic and morphological contexts.